Filipe de Magalhães: Magnificat Sexti Toni [odd verses] - Henriques, Luís (2021)
Edition of the "Magnificat Sexti Toni", for four voices, by the Portuguese composer Filipe de Magalhães (c.1571-1652). This work sets the polyphony for the odd verses of the canticle. It was published in Magalhães's "Cantica Beatissimae Virginis", printed in Lisbon at the Craesbeeck workshop in 1636.